The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/polym14122412
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Heat Treatment Atmosphere and Temperature on the Properties of Carbon Fibers

Abstract: In this study, carbon fibers were heat-treated in a nitrogen and oxygen atmosphere according to temperature to elucidate the mechanism of chemical state changes and oxygen functional group changes on the carbon fiber surface by analyzing the mechanical and chemical properties of carbon fibers. Carbon fibers before and after heat treatment were analyzed using FE-SEM (Field Emission Scanning), UTM (Universal Tensile Testers), XPS (X-ray Photoelectron Spectroscopy), and surface-free energy. In the nitrogen atmosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…However, it is easily oxidized under a high-temperature aerobic environment, which greatly weakens its comprehensive mechanical properties, and the stability of the composites declines sharply [ 23 , 24 ]. Gyungha Kim et al [ 25 ] explored the mechanical properties of carbon fibers after heat treatment in nitrogen and oxygen atmospheres. They found that the tensile strength at 500 °C was equivalent to that of the virgin carbon fibers in the nitrogen atmosphere, decreasing to 71% at 1000 °C.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is easily oxidized under a high-temperature aerobic environment, which greatly weakens its comprehensive mechanical properties, and the stability of the composites declines sharply [ 23 , 24 ]. Gyungha Kim et al [ 25 ] explored the mechanical properties of carbon fibers after heat treatment in nitrogen and oxygen atmospheres. They found that the tensile strength at 500 °C was equivalent to that of the virgin carbon fibers in the nitrogen atmosphere, decreasing to 71% at 1000 °C.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon fiber can still maintain good mechanical properties in an inert atmosphere above 2000 • C. However, it is easily oxidized under a high-temperature aerobic environment, which greatly weakens its comprehensive mechanical properties, and the stability of the composites declines sharply [23,24]. Gyungha Kim et al [25] explored the mechanical properties of carbon fibers after heat treatment in nitrogen and oxygen atmospheres. They found that the tensile strength at 500 • C was equivalent to that of the virgin carbon fibers in the nitrogen atmosphere, decreasing to 71% at 1000 • C. In the oxygen atmosphere, the tensile properties gradually decreased at 500 • C and the carbon fibers deteriorated above 600 • C, at which point the tensile properties were unable to be measured.…”
Section: Introductionmentioning
confidence: 99%
“…The optimum value of 0.51 at 10 s was about twice that of the APS. Other studies have reported that the surface activity of carbon fibers is enhanced when the O/C is higher than 0.26 [11]. As shown in Table . 2, the O/C of commercial carbon fibers is 0.28; thus, the recycled carbon fibers in this study are considered to have sufficiently introduced oxygen functional groups.…”
Section: Chemical Properties Of Recycled Carbon Fibersmentioning
confidence: 77%
“…Carbon fibers are lightweight materials with low density, high specific strength, heat resistance, and excellent thermal and electrical conductivity, and their applications are expected to expand not only in the aerospace industry but also in all industries in the future [1][2][3][4][5][6][7][8][9]. However, due to the high price of carbon fiber and the expensive manufacturing process, it is only used for expensive parts, such as aerospace, shipbuilding, and sporting goods, and it is difficult to expand its application to fields such as general commercial vehicles due to its high price [10,11]. In addition, carbon composites currently in use are made of thermosetting resins, which are difficult to recycle, and most are disposed of by landfill and incineration, causing environmental pollution [12].…”
Section: Introductionmentioning
confidence: 99%
“…In general, surface treatment includes wetting methods (liquid oxidation) such as sulfuric acid and nitric acid [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ], dry methods (dry gaseous oxidation) [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ] such as high-temperature treatment in an atmosphere of oxidizing gas or inert gas, electric oxidation methods [ 3 , 30 , 31 , 32 ], the plasma method [ 33 , 34 , 35 , 36 , 37 , 38 , 39 ] of surface treatment using ionized gas, and exposure to strong energy such as ozone and ultraviolet rays (energetic ions oxidation) [ 40 , 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%